Three new species of the leafhopper subfamily Iassinae (Hemiptera: Cicadellidae) from China - Wang, Xian-Yi; Wu, Yun-Fei; Dai, Ren-Huai (Zootaxa, 2018)
Three new species of leafhoppers: Siniassus hamulus sp. nov., Decliviassus sagittatus sp. nov., Krisna quadrimaculosus sp. nov. are described and illustrated from China. An updated checklist and key to 22 of the 24 known Chinese species of these three genera (Siniassus, Decliviassus, Krisna) are provided.